The Impact of Applying Corporate Governance Requirements on Financial Reports Quality of the Libyan Banks - محمد الأوجلي, جمعة; أحمد الكزة, عبد السلام; عبد القادر عامر, أنس (Dirasat in Economics and Business, 2024)
Previous research test the impact of corporate governance on different aspects of organizational systems and performance. This study aims to test the impact of the application of governance guidance issued by Libyan Central Bank on the quality of the financial reports of Libyan commercial banks. For this purpose, the study uses a multiple case study approach to deeply investigate and explore this supposed relationship. Semi-structured interviews with board members show that the participated banks are, to a very large extend, follow the Central Bank governance guidance. Moreover, the content analysis revealed that the application of corporate guidance has led to an improvement in the quality of the published financial reports.